Bacteria and the market. (September 2019) - Campbell, Norah; Deane, Cormac
We present a psychoanalytic reading of 332 images of bacteria in advertising for antibacterial products and in public service announcements since 1848. We identify four dominant and recurring tropes that bring bacteria into the symbolic realm: cuteness, overpopulation, the lower classes and deviant sex. As a first stage of our analysis, we propose that bacteria are symptoms of a capitalist socio-economic order. Bacteria are repressed fears and fantasies about purity, gender, race, community, pollution, class and sexual promiscuity which are tacitly leveraged by antibacterial brands. We then ask why these fears and fantasies take the form of the bacterial. We trace a movement from the psychoanalytical concept of the symptom to the sinthome. If symptoms can be read as a repressed, extrinsic ideology that can/must be revealed, the sinthome is a fantasy that, when brought to light, does not dissolve, because it structures reality intrinsically. We indicate an emerging body of psychoanalytically informed critical marketing that points to the perverse effects of emancipatory, revelatory critical analysis, where the consumer is made to face their symptom. The sinthome is a useful way to summarize this problem. However, while the sinthome is testimony to the impossibility of redemption through the revelation of our ideological prisons, it has a productive, positive contribution to critical marketing theory. It presents a theory of and a tool for analysing fantasies that focus on the form of their expression, rather than their content. In our case, the fact that fantasy takes the form of the bacterial reveals a surprising confluence between the politics of community and the physiology of (auto)immunity, with important and specific strategies on how ideology can be interrupted. This power of the sinthome to straddle the symbolic, imaginary and real creates ways to conceive marketing phenomena as simultaneously psychoanalytic, political, physical and metaphorical.